Human‐Specific Transcriptome of Ventral and Dorsal Midbrain Dopamine Neurons. Issue 6 (30th March 2020) - Monzón‐Sandoval, Jimena; Poggiolini, Ilaria; Ilmer, Tobias; Wade‐Martins, Richard; Webber, Caleb; Parkkinen, Laura
Abstract : Objective: Neuronal loss in the substantia nigra pars compacta (SNpc) in Parkinson disease (PD) is not uniform, as dopamine neurons from the ventral tier are lost more rapidly than those of the dorsal tier. Identifying the intrinsic differences that account for this differential vulnerability may provide a key for developing new treatments for PD. Methods: Here, we compared the RNA‐sequenced transcriptomes of 100 laser captured microdissected SNpc neurons from each tier from 7 healthy controls. Results: Expression levels of dopaminergic markers were similar across the tiers, whereas markers specific to the neighboring ventral tegmental area were virtually undetected. After accounting for unwanted sources of variation, we identified 106 differentially expressed genes (DEGs) between the SNpc tiers. The genes higher in the dorsal/resistant SNpc tier neurons displayed coordinated patterns of expression across the human brain, their protein products had more interactions than expected by chance, and they demonstrated evidence of functional convergence. No significant shared functionality was found for genes higher in the ventral/vulnerable SNpc tier. Surprisingly but importantly, none of the identified DEGs was among the familial PD genes or genome‐wide associated loci. Finally, we found some DEGs in opposite tier orientation between human and analogous mouse populations. Interpretation: Our results highlight functional enrichments of vesicular trafficking, ion transport/homeostasis and oxidative stress genes showing higher expression in the resistant neurons of the SNpc dorsal tier. Furthermore, the comparison of gene expression variation in human and mouse SNpc populations strongly argues for the need of human‐focused omics studies. ANN NEUROL 2020;87:853–868